Greed or grievance : why is South African youth crime so violent in nature? : First world taste on a third world budget or simply marginalised from centre-stage? - Boda, Siham (Institute of Criminology, 2014)
How can criminological theory assist in making sense of the youth subcultures that are involved in criminal activity of a violent nature in the contemporary South African context? - T.p. Includes bibliographical references (leaves 207-219).